Pengaruh Pandemi Covid 19, Financial Distress, Good Corporate Governance terhadap Manajemen Laba pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2018-2022 - Denisyah Azhura; Vanica Serly (Universitas Negeri Padang, 2024)
This research aims to test and determine the impact of the Covid 19 pandemic, financial distress, good corporate governance (independent board of commissioners and managerial ownership) on earnings management. Leverage and company size are control variables. This research uses companies operating in the manufacturing sector that are listed on the Indonesia Stock Exchange during the period 2018 to 2022. The sample used is 36 samples of manufacturing companies over a 5year period. This research uses descriptive statistical methods for data analysis. estimation for making panel regression models, model testing and hypothesis testing using the Eviews12 program. The research results show that the Covid 19 pandemic has a positive effect on earnings management, financial distress has no effect on earnings management, an independent board of commissioners has no effect on earnings management, and managerial ownership has no effect on earnings management.